Inflammatory Cytokines Associate With Neuroimaging After Acute Mild Traumatic Brain Injury - Edwards, Katie A.; Pattinson, Cassandra L.; Guedes, Vivian A.; Peyer, Jordan; Moore, Candace; Davis, Tara; Devoto, Christina; Turtzo, L. Christine; Latour, Lawrence; Gill, Jessica M. (Frontiers in Neurology, 2020)
Introduction: Elevated levels of blood-based proinflammatory cytokines are linked to acute moderate to severe traumatic brain injuries (TBIs), yet less is known in acute mild (m)TBI cohorts. The current study examined whether blood-based cytokines can differentiate patients with mTBI, with and without neuroimaging findings (CT and MRI). Material and Methods: Within 24 hours of a mTBI, determined by a Glasgow Coma Scale (GCS) between 13-15, participants (n=250) underwent a computed tomography (CT) and magnetic resonance imaging (MRI) scan and provided a blood sample. Participants were classified into three groups according to imaging findings; 1) CT+, 2) MRI+ (CT-), 3) Controls (CT-MRI-). Plasma levels of circulating cytokines (IL-6, IL-10, TNFα), and vascular endothelial growth factor (VEGF) were measured using an ultra-sensitive immunoassay. Results: Concentrations of inflammatory cytokines (IL-6, TNFα) and VEGF were elevated in CT+, as well as MRI+ groups (p<0.001), compared to controls, even after controlling for age, sex and cardiovascular disease (CVD)-related risk factors; hypertension, and hyperlipidemia. Postconcussive symptoms were associated with imaging groupings, but not inflammatory cytokines in this cohort. Levels of VEGF, IL-6, and TNFα differentiated patients with CT+ findings from controls, with the combined biomarker model (VEGF, IL-6, TNFα, and IL-10) showing good discriminatory power (AUC 0.92, 95% CI 0.87-0.97). IL-6 was a fair predictor of MRI+ findings compared to controls (AUC 0.70, 95% CI 0.60-0.78). Finally, the combined biomarker model discriminated patients with MRI+ from CT+ with an AUC of 0.71 (95% CI 0.62-0.80). Conclusions: When combined, IL-6, TNFα, and VEGF may provide a promising biomarker cytokine panel to differentiate mTBI patients with CT+ imaging versus controls. Singularly, IL-6 was a fair discriminator between each of the imaging groups. Future research directions may help elucidate mechanisms related to injury severity and potentially, recovery following an mTBI.